2009
DOI: 10.1002/jgm.1300
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity against porcine circovirus 2 in mice induced by a gene‐based combination vaccination

Abstract: This prime-boost vaccination strategy, using a gene gun for DNA priming and recombinant MVA for boosts, may be an attractive vaccine strategy against PCV2 infection in swine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Direct injection of plasmid DNA has been used as a promising approach to protect animals and humans against pathogens (34,35). DNA vaccines against PCV2 have been investigated, which often have limited efficacy and need two or three immunizations to achieve a good level of immunity (1,3,8). DNA vaccines often have limited efficacy.…”
mentioning
confidence: 99%
“…Direct injection of plasmid DNA has been used as a promising approach to protect animals and humans against pathogens (34,35). DNA vaccines against PCV2 have been investigated, which often have limited efficacy and need two or three immunizations to achieve a good level of immunity (1,3,8). DNA vaccines often have limited efficacy.…”
mentioning
confidence: 99%
“…The recombinant vaccines for PCV2 infection, in majority, use genetical manipulation in the sequence of ORF2 nucleotide that contains a region where the immunogenic epitopes of the virus are scripted [57][58][59][60]. Certain studies have used the strategy of DNA vaccine using ORF2 as the immunogen [61][62][63][64]. The DNA vaccines can be injected with the use of the traditional syringes or inoculated by the use of gene guns.…”
Section: Experimental Vaccinesmentioning
confidence: 99%
“…Although studies were developed in both preclinical and clinical stages for human and veterinary applications, a fixed prime-boost regimen is still not available. Recent publications from the veterinary field demonstrated that combination of a gene gun-mediated naked DNA vector as priming and MVA as booster in mice is an attractive line of attack against porcine circovirus type 2 (PCV2) [112]. A vaccination scheme for highly pathogenic avian influenza H5N1 (AsHP H5N1) virus revealed that priming with a fowlpox-vectored vaccine followed by a boost with inactivated vaccine stimulated a broader protection than two administrations of a fowlpox recombinant (vFP-H5 Asia) [113].…”
Section: What To Expect From the Prime-boost Approach?mentioning
confidence: 99%